2015
DOI: 10.1124/jpet.114.221622
|View full text |Cite
|
Sign up to set email alerts
|

2-Acetylcyclopentanone, an Enolate-Forming 1,3-Dicarbonyl Compound, Is Cytoprotective in Warm Ischemia-Reperfusion Injury of Rat Liver

Abstract: We have previously shown that 2-acetylcyclopentanone (2-ACP), an enolate-forming 1,3-dicarbonyl compound, provides protection in cell culture and animal models of oxidative stress. The pathophysiology of ischemia-reperfusion injury (IRI) involves oxidative stress, and, therefore, we determined the ability of 2-ACP to prevent this injury in a rat liver model. IRI was induced by clamping the portal vasculature for 45 minutes (ischemia phase), followed by recirculation for 180 minutes (reperfusion phase). This se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…In contrast, the 1,3-dicarbonyl enols (e.g., 2-ACP) and polyphenols (e.g., THA) are stable, non-toxic and relatively water soluble compounds (Ballantyne and Cawley, 2001; LoPachin et al, 2011; Zhang et al, 2013). Our present findings and recent studies demonstrating the ability of enolate-forming compounds to inhibit liver ischemia/reperfusion injury (Kosharskyy et al, 2015) suggest that 2-ACP, THA, PG and other enolate-forming derivatives might be viable platforms for development of new pharmacotherapeutic approaches to diseases, injury states or drug-induced toxicities that involve electrophile-mediated cellular damage.…”
Section: Discussionsupporting
confidence: 61%
“…In contrast, the 1,3-dicarbonyl enols (e.g., 2-ACP) and polyphenols (e.g., THA) are stable, non-toxic and relatively water soluble compounds (Ballantyne and Cawley, 2001; LoPachin et al, 2011; Zhang et al, 2013). Our present findings and recent studies demonstrating the ability of enolate-forming compounds to inhibit liver ischemia/reperfusion injury (Kosharskyy et al, 2015) suggest that 2-ACP, THA, PG and other enolate-forming derivatives might be viable platforms for development of new pharmacotherapeutic approaches to diseases, injury states or drug-induced toxicities that involve electrophile-mediated cellular damage.…”
Section: Discussionsupporting
confidence: 61%
“…These compounds ionize in aqueous solutions to form nucleophilic enolate anions, which can form 1,4-Michael adducts with ACR, HNE and other electrophilic unsaturated aldehydes involved in the oxidative stress-induced injury. Recently, it has been found that 2-ACP reduces the liver I/R damage in dosedependent manner by sequestering electrophilic species and in particular ACR, as indicated by the normalization of the I/R-altered liver histologic and biochemical parameters [40]. Hence, our results demonstrate that ACR is produced also in the liver I/R damage and, although partially neutralized by albumin and endogenous detoxificants, it can induce a damaging action.…”
Section: Discussionmentioning
confidence: 53%
“…Acrylamide (ACR), a water-soluble type-2 alkene, is used in different processes in the paper, textile, and cosmetics industry, as soil conditioner in mineral processing and mining, and as chemical sewer in grouting operations 1 . ACR induces neurotoxicity by depleting cellular glutathione (GSx) levels and by forming Michael type adducts with functionally critical nucleophilic sulfhydryl thiolate groups on cysteine residues of proteins in the synaptic terminals 2,3 . The loss of function of some relevant proteins directly involved in the synaptic vesicles recycling finally results in an altered synaptic function 3 .…”
Section: Introductionmentioning
confidence: 99%